Rice SUMO protease Overly Tolerant to Salt 1 targets the transcription factor, OsbZIP23 to promote drought tolerance in rice. (17th November 2017) - Srivastava, Anjil Kumar; Zhang, Cunjin; Caine, Robert S; Gray, Julie; Sadanandom, Ari
Summary: Conjugation of SUMO (Small Ubiquitin‐like Modifier) protein to cellular targets is emerging as a very influential protein modification system. Once covalently bound, SUMO conjugation can change the stability or functionality of its cognate target proteins. SUMO protease can rapidly reverse SUMO conjugation making this modification system highly dynamic. A major factor in the variation of SUMO‐target function is the balance between the conjugated/de‐conjugated forms. The mechanistic role of these regulatory SUMO proteases in mediating stress responses has not been defined in any crops. In this study, we reveal the role of the SUMO protease, OsOTS1 in mediating tolerance to drought in rice. OsOTS1 depleted transgenic plants accumulate more ABA and exhibit more productive agronomic traits during drought while OsOTS1 overexpressing lines are drought sensitive but ABA insensitive. Drought and ABA treatment stimulates the degradation of OsOTS1 protein indicating that SUMO conjugation is an important response to drought stress in rice achieved through down‐regulation of OTS1/2 activity. We reveal that OsOTS1 SUMO protease directly targets the ABA and drought responsive transcription factor OsbZIP23 for de‐SUMOylation affecting its stability. OsOTS ‐RNAi lines show increased abundance of OsbZIP23 and increased drought responsive gene expression while OsOTS1 overexpressing lines show reduced levels of OsbZIP23 leading to suppressed drought responsive gene expression. Our data reveal a mechanism in which rice plants govern ABA‐dependant drought responsive gene expression by controlling the stability of OsbZIP23 by SUMO conjugation through manipulating specific SUMO protease levels. Significance Statement: The mechanistic role of these regulatory SUMO proteases in mediating stress responses has not been defined in any crops. In this study, we reveal the role of the SUMO protease, OsOTS1 in mediating tolerance to drought in rice.